Practical carrier frequency offset estimation schemes for TD-SCDMA scanning receiver - Zhengbo Jiang; Ling Tian; Jin Liu; Wenhu Xu (2012 International Conference on Microwave and Millimeter Wave Technology, 2012)
Carrier frequency offset estimation and adjustment is essential to wireless communication receiver. Scanning receiver is both a receiver and a wireless communication measurement instrument, and carrier frequency offset affects both receiver performance and measurement accuracy. In this paper, we introduced a phase based algorithm for frequency offset estimation, experiments and analysis were also given to verify its effectivity and limitations. To compensate the drawback of phase based algorithm and to significantly improve the estimation accuracy, GPS based algorithm was also proposed in this paper.